Editorial: Solidarity and Sustainability in Architectural Engineering Technology - De Vita, Mariangela (International Journal of Architectural Engineering Technology, 2023)
Scientific progress in the construction sector must take care of safety and global well-being through updated construction techniques and methods, new materials, and design tools. In the last years, best practices linked to traditional techniques have developed thanks to technological and digital innovation which look at safety & security issues, the health of people and the planet. For these reasons, research in the field of architectural engineering has to put technological innovation at the service of eco-compatible buildings and cities, imagining new ways to ensure equitable access to natural resources, based on sustainable development and responsible consumption.